DNA damage repair kinase DNA‐PK and cGAS synergize to induce cancer‐related inflammation in glioblastoma. (27th December 2022) - Taffoni, Clara; Marines, Johanna; Chamma, Hanane; Guha, Soumyabrata; Saccas, Mathilde; Bouzid, Amel; Valadao, Ana‐Luiza Chaves; Maghe, Clément; Jardine, Jane; Park, Mi Kyung; Polak, Katarzyna; De Martino, Mara; et al.
Abstract: Cytosolic DNA promotes inflammatory responses upon detection by the cyclic GMP‐AMP (cGAMP) synthase (cGAS). It has been suggested that cGAS downregulation is an immune escape strategy harnessed by tumor cells. Here, we used glioblastoma cells that show undetectable cGAS levels to address if alternative DNA detection pathways can promote pro‐inflammatory signaling. We show that the DNA‐PK DNA repair complex (i) drives cGAS‐independent IRF3‐mediated type I Interferon responses and (ii) that its catalytic activity is required for cGAS‐dependent cGAMP production and optimal downstream signaling. We further show that the cooperation between DNA‐PK and cGAS favors the expression of chemokines that promote macrophage recruitment in the tumor microenvironment in a glioblastoma model, a process that impairs early tumorigenesis but correlates with poor outcome in glioblastoma patients. Thus, our study supports that cGAS‐dependent signaling is acquired during tumorigenesis and that cGAS and DNA‐PK activities should be analyzed concertedly to predict the impact of strategies aiming to boost tumor immunogenicity. Synopsis: Upon cytosolic DNA detection, the DNA damage repair kinase DNA‐PK promotes optimal type I Interferon and chemokine production by regulating IRF3 activation and enabling cGAS‐dependent cGAMP production. This cooperation fuels cancer‐mediated inflammation, affecting both tumour initiation and patient prognosis. DNA‐PK promotes STING‐independent IRF3‐dependent type I Interferon responses. DNA‐PK enhances genotoxic stress‐dependent type I Interferon signaling in the absence of cGAS. DNA‐PK and cGAS cooperate for optimal type I Interferon responses and chemokine/cytokine production. DNA‐PK enables cGAS‐dependent cGAMP production. cGAS expression compromises early tumorigenesis but promotes cancer‐associated chronic inflammation. Abstract : DNA‐PK cooperates with cGAS‐STING signalling to regulate type I Interferons, chemokines and tumor‐related inflammatory responses.